Performance of a diflufenican-containing premixture in dicamba-resistant soybean systems - Matthew C. Woolard; Jason K. Norsworthy; Trenton L. Roberts; L. Tom Barber; Benjamin C. Thrash; Christy L. Sprague; Amar S. Godar (Weed Technology)
Weeds belonging to the Amaranthus family are most problematic for soybean producers. With Palmer amaranth evolving resistance to multiple herbicides labeled for use in soybean, producers seek new sites of action to integrate into season-long herbicide programs. Bayer CropScience plans to launch a Convintro™ brand of herbicides, one being a premixture that will include diflufenican (categorized as a Group 12 herbicide by the Weed Science Society of America [WSSA]), metribuzin (WSSA Group 5), and flufenacet (WSSA Group 15), for use preemergence in soybean. Research trials were conducted in Fayetteville and Keiser, AR, and Holt, MI, in 2022 and 2023, to evaluate the premixture in a season-long program in a dicamba-resistant soybean system. A 0.17:0.35:0.48 ratio of a premixture of diflufenican:metribuzin:flufenacet (DFF-containing premixture) was applied preemergence with different combinations of glyphosate, glufosinate, dicamba, and acetochlor at 28 (early postemergence) and 42 (late postermergence) days after planting (DAP). At the early postemergence timing, the DFF-containing premixture provided >90% control of Palmer amaranth and prickly sida. However, common ragweed, common lambsquarters, morningglory ssp., and annual grass control was ≤80% at this timing. When the late postemergence applications occurred, treatments that had already received an early postemergence application controlled prickly sida, morningglory ssp., Palmer amaranth, and annual grasses to a greater extent than those that had not, indicating the preemergence application of the DFF-containing premixture was not sufficient to provide control of the weed spectrum through 42 DAP. By 70 DAP, all programs provided ≥93% control of all weeds evaluated. Herbicide programs that included the DFF-containing premixture preemergence followed by (fb) EPOST fb LPOST common ragweed, common lambsquarters, morningglory ssp., and annual grasses to a greater than the one-pass postemergence systems. In addition, all herbicide programs evaluated in this study reduced Palmer amaranth seed production by >99%. However, producers who plan to use the DFF-containing premixture may need two postemergence herbicide applications to obtain high levels of weed control throughout the growing season.